2017
DOI: 10.1177/0363546516687750
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Neuromuscular Control Protects Against Hamstring Injuries in Male Soccer Players: A Prospective Study With Electromyography Time-Series Analysis During Maximal Sprinting

Abstract: Muscle activity of the core unit during explosive running appeared to be associated with hamstring injury occurrence in male soccer players. Higher amounts of gluteal and trunk muscle activity during the airborne phases of sprinting were associated with a lower risk of hamstring injuries during follow-up. Hence, the present results provide a basis for improved, evidence-based rehabilitation and prevention, particularly focusing on increasing neuromuscular control of the gluteal and trunk muscles during sport-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 39 publications
1
71
1
2
Order By: Relevance
“…The same authors also found differences in muscle excitation between subsequently injured and uninjured soccer athletes, that were again constrained to the swing phase. 65 During mid-swing, injured athletes showed significantly lower muscle excitation of the trunk, and lower gluteal excitation during late swing. Again, no differences were observed between injured and non-injured athletes during stance.…”
Section: During Late Swing Phasementioning
confidence: 96%
See 1 more Smart Citation
“…The same authors also found differences in muscle excitation between subsequently injured and uninjured soccer athletes, that were again constrained to the swing phase. 65 During mid-swing, injured athletes showed significantly lower muscle excitation of the trunk, and lower gluteal excitation during late swing. Again, no differences were observed between injured and non-injured athletes during stance.…”
Section: During Late Swing Phasementioning
confidence: 96%
“…No kinematic differences were found between subsequently injured and uninjured athletes during the stance phase. The same authors also found differences in muscle excitation between subsequently injured and uninjured soccer athletes, that were again constrained to the swing phase . During mid‐swing, injured athletes showed significantly lower muscle excitation of the trunk, and lower gluteal excitation during late swing.…”
Section: The Potential For Injury During Late Swing Phasementioning
confidence: 99%
“…Concerns also exist of whether evidence-based interventions are actually adopted within professional clubs (Bahr et al, 2015) or if reporting of time lost to HSI is more sensitive (Eirale, 2018), making accurate comparison with previous decades challenging. The apparent ongoing rise in HSI is clearly complex, and although there is general consensus on the multi-factorial aetiology of HSI (Sole et al, 2008;Thorborg, 2014), this extensive (Opar et al, 2012) and increasing list of risk factors (Mendiguchía et al, 2015;Schuermans et al, 2017a;Timmins et al, 2015a), may only appear to further confound those seeking to keep their players injury free. Therefore, despite extensive sports injury research, which has arguably stemmed the tide of injury as a whole, the complex and sustained problem of HSI not only endures, but worsens.…”
Section: The Paradoxmentioning
confidence: 99%
“…Recent studies suggest that the timing of hamstring muscle activation and the timing and amplitude of gluteal and abdominal muscle activation are important for preventing hamstring injuries. Both can be improved by plyometric exercises . These exercises strengthen the elastic properties of connective tissue, increase motor unit activation, increase passive tension of the muscle‐tendon complex, and improve cross‐bridge mechanics .…”
Section: Introductionmentioning
confidence: 99%
“…Both can be improved by plyometric exercises. 19,20 These exercises strengthen the elastic properties of connective tissue, increase motor unit activation, increase passive tension of the muscle-tendon complex, and improve cross-bridge mechanics. 21,22 This improves eccentric strength, joint stiffness, and neuromuscular control, all variables associated with the occurrence of hamstring injuries.…”
Section: Introductionmentioning
confidence: 99%